A dog called Kitty - Wallace, Bill, 1947- (New York : Holiday House, 2005)
Afraid of dogs since he was attacked by a mad one, Ricky resists taking in a homeless pup that shows up at the farm.
G5
Keywords: Dogs -- Fiction